Hematotoxicity of Co-Administration of Bisphenol A and Acetaminophen in Rats and its Amelioration by Melatonin - Akhter, Mohammad S.; Rashid, Hina; Hamali, Hassan A.; Alshahrani, Saeed; Dobie, Gasim; Qadri, Marwa; Madkhali, Aymen M.; Mobarki, Abdullah A. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Hematotoxicity is an underexplored endpoint of toxicity in most of the chemical exposures. An adverse effect on the hematological system arising out of xenobiotic exposure causes impaired hemostasis and coagulation leading to disease. BPA and acetaminophen are widely used synthetic chemicals worldwide and both are known and have numerous toxic effects. Since both can be simultaneously exposed to humans over a period of time, we hypothesized that their exposure can cause hematotoxicity, which may be ameliorated by melatonin. Objective: In the current study, we aimed to find the effect of single and co-treatment of bisphenol A and acetaminophen on the RBC and coagulation factors in rats, and amelioration of impairment by melatonin. Methods: Oxidative stress in red blood cells, bleeding time, blood clotting time, prothrombin time, partial thromboplastin time, and fibrinogen levels were assessed as indicators of hematotoxicity with single and co-exposure to bisphenol A and acetaminophen in rats. The effect of melatonin as a hemato-protective agent was assessed in the co-exposure. Results: An increase in RBC oxidative stress and decrease in bleeding time, blood clotting time, prothrombin time, and partial thromboplastin time along with an increase in fibrinogen levels were observed with bisphenol A and acetaminophen treatment, which were further aggravated with cotreatment of the two. Melatonin treatment, however, was seen to decrease the increase in oxidative stress and ameliorate the impairment in coagulation factors. Conclusion: Bisphenol A and acetaminophen cause an increase in the oxidative stress in the red blood cells, and cause a shift toward pro-coagulation, which is alleviated by treatment with melatonin.
Keywords: acetaminophen